2023
DOI: 10.2147/ijn.s382109
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Polydopamine-Liposome Nanoformulation as an Effective Anti-Breast Cancer Therapy

Abstract: Introduction Drug delivery systems (DDSs) based on liposomes are potential tools to minimize the side effects and substantially enhance the therapeutic efficacy of chemotherapy. However, it is challenging to achieve biosafe, accurate, and efficient cancer therapy of liposomes with single function or single mechanism. To solve this problem, we designed a multifunctional and multimechanism nanoplatform based on polydopamine (PDA)-coated liposomes for accurate and efficient combinatorial cancer thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…The cardiomyocytes histoarchitecture in AF-PDA-DOX@TNP group was similar to normal cardiac tissue [23].…”
Section: Histopathologicalmentioning
confidence: 59%
“…The cardiomyocytes histoarchitecture in AF-PDA-DOX@TNP group was similar to normal cardiac tissue [23].…”
Section: Histopathologicalmentioning
confidence: 59%
“…This behavior has been ascribed to a possible decomposition of the polymeric layer in acidic conditions, but this topic is still under debate. Finally, the release of drugs from PDA-coated liposomes was stimulated by NIR radiation, likely due to the heat generated by the photothermal effect …”
Section: Pda and Liposomes: Ameliorative Effects Of Pda Coatingsmentioning
confidence: 99%
“…The strategies proposed to obtain a PDA coating on the surface of isolated liposomes are quite simple and generally follow the same scheme. Commonly, the strong templating effect of liposomes is exploited by simply inducing the in situ polymerization of DA in a liposomal suspension in TRIS buffer at pH 8.5 ,,,, or phosphate buffer at pH 8.0 (Figure B). , In fact, it has been observed that to ensure a good PDA coating, it is important that the anchoring takes place at an early stage of the polymerization process or, better, that the polymerization is performed in the presence of the vesicles to be coated. Indeed, when the PDA particles are already formed, the majority of uncyclized aminoethyl groups have already converted to indoles, which are less prone to adhesion .…”
Section: Pda-modified Liposomes: Preparationmentioning
confidence: 99%
“…Additionally, liposomal nanoformulation of DOX and ICG was done through their PEGylation and further coated with polydopamine (PDA), which resulted in the formation of PDA@Lipo/DOX/ICG nanoparticle. This nanoparticle was reported to exhibit remarkable anti-cancer therapeutic efficacy after being subjected to irradiation for PDT [34]. Lipid nanoparticles (LNPs) have also emerged as one of the most cutting-edge methods for the effective in vivo administration of exogenous mRNA vaccine.…”
Section: Lipid-mediated Nanoformulations Of Anti-cancer Drugsmentioning
confidence: 99%